Numerical Analysis of a New Block-Type Rail Bearing Beam for the Mid-Low-Speed Maglev Train - Wubin Wang; Yandong Li; Kang Xie; Zhichao Huang; Linchuan Shi (Advances in Civil Engineering)
In this study, a new block-type rail bearing beam is presented, which consists of a cast-in-place base and prefabricated blocks. The finite element analysis is conducted to assess the proposed new rail bearing beam structure. The performed finite element method (FEM) simulation focused on the dynamic stress at the bottom of the rail bearing beam and structural internal force and deformation under the case of train loading, etc. Besides, the relationship between first-order natural frequency and activation frequency in the new support rail beam structure is analyzed and the beneficial effects on the internode connection structure are quantified. The results show that the increase in driving speed has the most significant effect on the vertical acceleration of the structure, and the self-vibration frequency of the structure is relatively large, which means the structure is safe. Since previous research seldom focuses on this block-type rail bearing beam, this study lays a valuable foundation for the construction of a rail bearing beam for the mid-low-speed maglev train.